The differences between static stretching and proprioceptive neuromuscular facilitation stretching on flexibility: a gender review - Fenanlampir, Albertus; Lumba, Andreas J. F; Mutohir, Toho Cholik; Jiménez, José Vicente García (Jurnal Keolahragaan, 2024)
Proprioceptive neuromuscular facilitation (PNF) is the latest method used in flexibility training. This study shows something different from other studies.  The purpose of this study was whether there were differences in flexibility in male and female students as a result of the static stretching training method and the PNF stretching training method. The samples in this study were 80 male and female students, which were taken randomly from the male population of 56 people and the female population of 45 people, so that a total of 101 people. The results showed that the two methods showed a significant improvement. However, the PNF stretching training method was more effective than the static stretching training method in increasing flexibility. Both applied to male students and female students. Although the PNF stretching training method has been proven to increase flexibility in both males and females, students and physical education teachers need to pay attention to this training method and do it regularly and continuously by considering the advantages and disadvantages of each method. The suggestions for further research are to carry out further, complete research, which is related to this research, by taking into account the essential differences between males and females, such as physical and physiological growth and development.